The combined effects of growth and maturity status on injury risk in an elite football academy - Xabier Monasterio; Sean Cumming; Jon Larruskain; David M. Johnson; Susana M. Gil; Iraia Bidaurrazaga-Letona; Jose A. Lekue; Gontzal Diaz-Beitia; Juan M. Santisteban; Sean Williams (Termedia Publishing House, 2023)
This study aimed to explore the interaction between growth rate on specific injury incidence and burden on pre-, circa- and post-peak height velocity (PHV) periods. Injury and stature data collected during the 2000-2020 seasons in an elite football academy were retrospectively analysed. Only players with height measurements from childhood until the attainment of adult height were included in the study (N = 84). Growth data were smoothed using a cubic spline to calculate daily growth rate and height. Growth rate was categorised into three groups: fast (> 7.2 cm/year), moderate (3.5-7.2 cm/year) and slow (< 3.5 cm/year). Percentage of observed adult height was used to classify players as pre-PHV ( 95%). Overall and specific injury incidence and burden and rate ratios for comparisons between growth rate groups were calculated on pre-, circa- and post-PHV periods, separately. Overall injury incidence and burden were greater in pre-PHV players with quicker growth rates compared to players growing moderately and slowly. All in all, players with more rapid growth-rates were at higher risk for growth-related injuries in all pre-, circa- and post-PHV periods. Post-PHV, the incidence and burden of joint/ligament injuries were 2.4 and 2.6-times greater in players growing slowly compared to players growing moderately. Practitioners should monitor growth rate and maturity status and consider their interaction to facilitate the design of targeted injury risk reduction strategies.